Software Tools of the Computis European Project to Process Mass Spectrometry Images. Issue 5 (October 2014) - Robbe, Marie-France; Both, Jean-Pierre; Prideaux, Brendan; Klinkert, Ivo; Picaud, Vincent; Schramm, Thorsten; Hester, Alfons; Guevara, Victor; Stoeckli, Markus; Roempp, Andreas; Heeren, Ron M.A.; Spengler, Bernhard; et al.
Among the needs usually expressed by teams using mass spectrometry imaging, one that often arises is that for user-friendly software able to manage huge data volumes quickly and to provide efficient assistance for the interpretation of data. To answer this need, the Computis European project developed several complementary software tools to process mass spectrometry imaging data. Data Cube Explorer provides a simple spatial and spectral exploration for matrix-assisted laser desorption/ionisation–time of flight (MALDI-ToF) and time of flight–secondary-ion mass spectrometry (ToF-SIMS) data. SpectViewer offers visualisation functions, assistance to the interpretation of data, classification functionalities, peak list extraction to interrogate biological database and image overlay, and it can process data issued from MALDI-ToF, ToF-SIMS and desorption electrospray ionisation (DESI) equipment. EasyReg2D is able to register two images, in American Standard Code for Information Interchange (ASCII) format, issued from different technologies. The collaboration between the teams was hampered by the multiplicity of equipment and data formats, so the project also developed a common data format (imzML) to facilitate the exchange of experimental data and their interpretation by the different software tools. The BioMap platform for visualisation and exploration of MALDI-ToF and DESI images was adapted to parse imzML files, enabling its access to all project partners and, more globally, to a larger community of users. Considering the huge advantages brought by the imzML standard format, a specific editor (vBrowser) for imzML files and converters from proprietary formats to imzML were developed to enable the use of the imzML format by a broad scientific community. This initiative paves the way toward the development of a large panel of software tools able to process mass spectrometry imaging datasets in the future.